Bioinformatic analysis reveals potential relationship between chondrocyte senescence and protein glycosylation in osteoarthritis pathogenesis - Yoshimoto, Makoto; Sadamori, Koki; Tokumura, Kazuya; Tanaka, Yuki; Fukasawa, Kazuya; Hinoi, Eiichi (Frontiers in Endocrinology, 2023)
Osteoarthritis (OA) is the most common degenerative and progressive joint disease. Cellular senescence is an irreversible cell cycle arrest progressive with age, while protein glycosylation is the most abundant post-translational modification, regulating various cellular and biological pathways. The implication of either chondrocyte senescence or protein glycosylation in the OA pathogenesis has been extensively and individually studied. In this study, we aimed to investigate the possible relationship between chondrocyte senescence and protein glycosylation on the pathogenesis of OA using single-cell RNA sequencing datasets of clinical OA specimens deposited in the Gene Expression Omnibus database with a different cohort. We demonstrated that both cellular senescence signal and protein glycosylation pathways in chondrocytes are validly associated with OA pathogenesis. In addition, the cellular senescence signal is well-connected to the O-linked glycosylation pathway in OA chondrocyte and vice-versa. The expression levels of the polypeptide N-acetylgalactosaminyltransferase (GALNT) family, which is essential for the biosynthesis of O-Glycans at the early stage, are highly upregulated in OA chondrocytes. Moreover, the expression levels of the GALNT family are prominently associated with chondrocyte senescence as well as pathological features of OA. Collectively, these findings uncover a crucial relationship between chondrocyte senescence and O-linked glycosylation on the OA pathophysiology, thereby revealing a potential target for OA.